Differentially Expressed Proteins of Soybean (Glycine max) Pulvinus in Light and Dark Conditions - Hakme Lee; Wesley M. Garrett; Joe H. Sullivan; Irwin Forseth; Savithiry Natarajan (Journal of Basic & Applied Sciences, 2013)
Some plant species both track and avoid the sun through turgor changes of the pulvinus tissue at the base of their leaves, maximizing light reception in dim conditions and minimizing cellular damage due to excessive light. Pulvinar response is known to be affected by both diurnally varying environmental factors and circadian patterns. Differential expression of the proteins between light and darkness are not well-known. In this study we used two-dimensional gel electrophoresis and mass spectrometry to separate and identify proteins in the soybean leaf pulvinus that were differentially expressed in the light compared to a dark control. Out of 165 protein spots previously identified (data not shown) 11 were found to have decreased expression in the light and 7 had increased light expression. The proteins that were more highly expressed in the light were mostly stress response proteins, while the under-expressed proteins were categorized as energy proteins. While the higher levels of expression of stress response proteins in the light align with other studies, the under-expressed light proteins require further examination to rule out artefactual results. These findings can provide a better understanding of the circadian pattern of protein expression in the legume pulvinus proteome.